Relationship between Pediculosis Capitis Incident and Age in female students of PPMI Assalaam Sukoharjo - Nadira As'ad; Bambang Sukilarso; Sri Haryati (Nexus Kedokteran Komunitas, 2017)
Introduction: Pediculus humanus var. capitis or head louse is an ectoparasite that can cause infestation on the hair and make pediculosis capitis. The infestations happened directly by contact to a person with pediculosis capitis and not directly by things like combs, pillows, or clothes. The older a person is, the level of knowledge they have are better and wider. Age related habits are assumed of being the cause of pediculosis. Mainly, habits like sharing personal stuffs and close contact with the age group in long time. The high prevalence of pediculosis capitis in boarding school cause students feel down, negative social perception, degrading sleep quality, and academic disturbance. This research aimed to determine the relationship between pediculosis capitis incident and age in female students of PPMI Assalaam. Methods: This study was analytic study with cross sectional approach. The research was done in 90 female students age 12-18 years old that divided into 3 groups of age. The sampling technique used stratified random sampling. Pediculosis capitis incident examined by using louse comb directly to the female students hair. Data was analyzed with SPSS 16.0 for Windows using chi square test. Result: Chi square test with significant level of 5% output p 0.076 (>0.05) so Ho accepted, it means that there is no relation between pediculosis capitis incident and age in female students of PPMI Assalaam. Conclusions: there is no significant relationship between pediculosis capitis incident and age in female students of PPMI Assalaam. Keywords: pediculosis capitis, female students, boarding school, age